Immune phenotype is differentially affected by changing the type of bovine respiratory disease vaccine administered at revaccination in beef heifers - Reddout, Cassidy; Hernandez, Lily P.; Chase, Christopher C. L.; Beck, Paul; White, Frank; Salak-Johnson, Janeen L. (Frontiers in Veterinary Science, 2023)
During preconditioning, modified-live vaccines are frequently administered to beef calves before weaning. In this study, we began to characterize the immune phenotype of calves that received a modified-live vaccination at 3-4 months of age and then either received the same modified-live or an inactivated vaccine upon arrival at the feedlot (weaning) and 28 days post-arrival (booster). Innate and adaptive immune measures were assessed before revaccination and 14 and 28 days post. Heifers that received three doses of the modified-live vaccine exhibited a relatively balanced immune response based on increases in mean cytokine concentrations (IL-17, IL-21) and total immunoglobulin-G (IgG) and subsets IgG1 and IgG2, which are related to both arms of the adaptive immune system. Conversely, heifers that received one dose of modified live and two doses of the inactivated vaccine had a more robust neutrophil chemotactic response and greater serum-neutralizing antibody titers, resulting in an enhanced innate immune and a skewed proinflammatory response. These results indicate that the revaccination protocol used after initial vaccination with a modified-live vaccine differentially influences the immune phenotype of beef calves, with three doses of modified live inducing a balanced immune response and a combination of modified live and inactivated vaccines inducing a skewed response. However, more research is needed to determine the protective efficacy of these vaccination protocols against disease.